Physiological bases for texture and color changes in fresh-cut ‘rocha’ pear: implications for the development of products and processes - Gomes, Maria Helena (2013)
Proceedings of the International Conference “Environmentally friendly and safe technologies for quality of fruit and vegetables”, held in Universidade do Algarve, Faro, Portugal, on January 14-16, 2009. This Conference was a join activity with COST Action 924.